MISCELLANEOUS BOTANICAL NOTES 4 ) - KOSTERMANS, A. J. G. H. (Research Center for Biology, 1965)
THE OLDEST SCIENTIFIC NAME FOR THE CINNAMON TREE Cinnamomum zeylanicum BL, 1826, has been currently considered to be the proper name for the common cinnamon tree.This name was already in use during the pre-Linnean period (cf. Kostermans, Bibliogr. Laur. 364.1964).The oldest valid name, however, is Cinnamomum verum J.S. Presl,1825, This is not a pharmaceutical name, as is evident from the references cited by Presl and by the treatment of other species. For complete references cf. Kostermans, Bibl. Laur. 360, 1964.